The spread and persistence of exotic phytoseiid, typhlodromahs aripo de leon (acari: phytoseiidae) and its effect on cassava green mite in Kenya - Kariuki, C.W.; Hanna, R.; Toko, M.; Ngari, B.M. (International Society for Tropical Root Crops, 2007)
Cassava green mite, Mononychellus tanajoa (Bondar) has been a major pest of cassava since its accidental introduction in Africa. Studies conducted recently on its biological control in the major cassava growing areas in Kenya demonstrate definite establishment of Typhlodromalus aripo in Kenya. This exotic predatory mite was not only found to have established and persisted since its introduction in 199516, but have also over the years spread widely to far distant from the original release sites in western and coastal regions. Where present, T. aripo is still persisting with a percentage presence varying between 0.33 and 100% and with a mean density of approximately 0.1 to 8.9 adults per tip. Consequently, a general trend of decline in the CGM population has also been observed over the years from a mean of approximately 60 to less than 30 mites per leaf. A similar trend was observed with CGM infestation levels. However there are a few areas where it has failed or has temporary established possibly due to factors related to unfavourable weather conditions, lack of cassava on the ground or isolated cassava fields, and cassava variety with characteristics unsuitable in sustaining T. aripo. Studies have also shown its ability to establish in newly planted cassava fields and thereby reducing CGM population from approximately 80 - 300 adults per leaf to below 50 and maintaining it below this level until the time of harvest in both local and improved cassava cultivars.